Effects of organic pollution and physical stress on benthic macroinvertebrate communities from two intermittently closed and open coastal lagoons (ICOLLs). (20th December 2015) - Coelho, Susana; Pérez-Ruzafa, Angel; Gamito, Sofia
Abstract: Benthic macroinvertebrate communities and environmental conditions were studied in two intermittently closed and open coastal lakes and lagoons (ICOLLs), located in southern Algarve (Foz do Almargem e Salgados), with the purpose of evaluating the effects of organic pollution, originated mainly from wastewater discharges, and the physical stress caused by the irregular opening of the lagoons. Most of the year, lagoons were isolated from the sea, receiving the freshwater inputs from small rivers and in Salgados, also from the effluents of a wastewater plant. According to environmental and biotic conditions, Foz do Almargem presented a greater marine influence and a lower trophic state (mesotrophic) than Salgados (hypereutrophic). Benthic macroinvertebrate communities in the lagoons were distinct, just as their relations with environmental parameters. Mollusca were the most abundant macroinvertebrates in Foz do Almargem, while Insecta, Oligochaeta and Crustacea were more relevant in Salgados. Corophium multisetosum occurred exclusively in Salgados stations and, just as Chironomus sp., other Insecta and Oligochaeta, densities were positively related to total phosphorus, clay content and chlorophyll a concentration in the sediment, chlorophyll a concentration in water and with total dissolved inorganic nitrogen. Abra segmentum, Cerastoderma glaucum, Peringia ulvae and Ecrobia ventrosa occurred only in Foz do Almargem, with lower values of the above mentioned parameters. Both lagoons were dominated by deposit feeders and taxa tolerant to environmental stress, although in Salgados there was a greater occurrence of opportunistic taxa associated to pronounced unbalanced situations, due to excess organic matter enrichment. Highlights: Foz do Almargem and Salgados are two ICOLLs in Southern Portugal studied for 1 year. They are small sized lagoons intermittently opened for 63 and 32 days respectively. Foz do Almargem has very reduced diversity, dominated by euryhaline mollusks. Hypereutrophic Salgados is dominated by few insects and by oligochaetes. Physical disturbance and excessive nutrients' load are the main disturbing factors.